2018
DOI: 10.1002/cphc.201701132
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Substituted Benzamides and Substituted Benzoic Acids: Like Tree, Like Fruit?

Abstract: Structure-property analyses of thermodynamic properties in chemical families of R-substituted benzamides, R-substituted benzoic acids, as well as R-substituted benzenes have been performed. The general linear interrelations for the vaporization enthalpies and the gas-phase enthalpies of formation between the chemical families under study have been established. These linear correlations provide a simple method for prediction of thermodynamic properties for benzenes with various combination of R-group substituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…For diphenyl ether, our calculations are in agreement with the results of Lukyanova et al, while the value reported by Emel’yanenko et al is about 4 kJ·mol –1 lower and slightly outside of the uncertainty bounds. A similar deviation (3.2 to 5.7 kJ·mol –1 ) is observed for nitrobenzamides studied in the same laboratory, although the experimental uncertainties in that case are higher.…”
Section: Results and Discussionsupporting
confidence: 79%
“…For diphenyl ether, our calculations are in agreement with the results of Lukyanova et al, while the value reported by Emel’yanenko et al is about 4 kJ·mol –1 lower and slightly outside of the uncertainty bounds. A similar deviation (3.2 to 5.7 kJ·mol –1 ) is observed for nitrobenzamides studied in the same laboratory, although the experimental uncertainties in that case are higher.…”
Section: Results and Discussionsupporting
confidence: 79%
“…For example, the structureproperty analysis of thermodynamic properties in chemical families of R-substituted benzamides and R-substituted benzoic acids has revealed simple linear behaviour. 70 These linear correlations are useful to establish an internal consistency of experimental results available for each chemical series. The linear correlations were also observed for thermochemical properties of organometallic compounds.…”
Section: 1mentioning
confidence: 99%
“…The general linear relationships of thermochemical and thermodynamic properties (for example, gas-phase enthalpies of formation or enthalpies of vaporization) between chemical families are well known for organic compounds. For example, analysis of the "structure-property" relationship in the chemical families of R-substituted benzamides and R-substituted benzoic acids revealed a simple linear behavior [74]. These linear correlations are useful in establishing the internal consistency of the experimental results available for each chemical series.…”
Section: Structure-property Relationships In Metal(iii) Acetylacetona...mentioning
confidence: 99%